O insustentável peso da legitimidade fiscal: administração fazendária na crise da monarquia portuguesa e independência no Brasil (1820-1825) (Ágora Journal, 2025)
The crisis of the Portuguese monarchy in America with the advent of constitutionalism changed the political and jurisdictional scenario in Brazil, culminating in the installation of provisional governments in the provinces and disputes over various political projects. The conflicts included discussions about the legitimacy of the monarchy and the fiscal crisis experienced in various parts of the country. At the same time, political uncertainty led to the unavailability of resources and the absence of tax remittances from the provinces to the center of the territory. By analyzing the conflicts surrounding the provincial Finance Boards and the disputes over jurisdiction with the provincial governments, we will analyze the weight of fiscal legitimacy during the process of political emancipation in Brazil.
Keywords: Finance Boards; fiscal legitimacy; independence